Investigation of common insertion hand postures and directions and determination of the voluntarily maximal and preferred insertion forces in automotive assembly tasks - Lee, Kyung Sun; Jung, Myung Chul (Human Factors and Ergonomics In Manufacturing, 2020)
The aim of this study was to investigate common insertion hand postures and directions (study 1) and determine the maximal and preferred insertion forces (study 2) for assembly workers. Video analyses were conducted to investigate the insertion hand posture and direction according to assembly materials. The results of the video analyses revealed that the left and right hands used five and six types of hand postures, respectively, with the maximum frequency, and this accounted for 86.7% and 81.4% of the postures, respectively. Forty male subjects participated in a psychophysical methodology test in which they were asked to perform insertion tasks by selecting the magnitudes such that the maximal acceptable forces (MAFs) and preferred forces (PFs) could be determined. The results indicated that hand posture, insertion direction, and age significantly affected MAFs. Furthermore, hand posture, insertion direction, and age significantly affected PFs. The insertion force should be considered in the task design phase, especially hand posture, insertion direction, and age.
Keywords: Assembly materials; Assembly workers; Automotive assemblies; Hand posture; insertion task; maximal acceptable force; Maximum frequency; preferred force; age; hand posture; insertion task; maximal acceptable force; preferred force